Academic performance, teacher assessment and student-teacher interaction in online versus face-to-face teaching - Fernández-Castro , Alejandro M. (2023)
Introduction: the change in the learning environment, from face-to-face to online, caused by the SARS-COV2 coronavirus pandemic in the Singapore university environment had an impact on academic performance, teacher assessment and student-teacher interaction. Objective: to evaluate the impact of the change in the learning environment on academic performance, teacher assessment and student-teacher interaction. Method: the grades and evaluation surveys of 282 students from two cohorts who studied in 2020 were compared consecutively face-to-face and online university training. Results: the results show differences in academic performance, but not the teacher’s assessment and student-teacher interaction. Discussion: it is possible to maintain an optimal educational quality without altering the teacher’s assessment  and the student-teacher interaction, both in the online and face-to-face modes, but it is necessary to present an evaluation method consistent with the modality used.